Clinical efficacy of intra-articular injections in knee osteoarthritis: a prospective randomized study comparing hyaluronic acid and betamethasone - Trueba Davalillo CA; Trueba Vasavilbaso C; Navarrete Álvarez JM; Coronel Granado P; García Jiménez OA; Gimeno del Sol M; Gil Orbezo F (Open Access Rheumatology: Research and Reviews, 2015)
Cesáreo Ángel Trueba Davalillo,1,2 Cesáreo Trueba Vasavilbaso,2 José Mario Navarrete Álvarez,2 Pilar Coronel Granado,3 Ozcar Alejandro García Jiménez,2 Mercedes Gimeno del Sol,3 Félix Gil Orbezo2 1School of Medicine (UNAM), México DF, Mexico; 2Orthopedic Service, Hospital Español de México, México DF, Mexico; 3Scientific Department, TEDEC-MEIJI FARMA,SA, Alcalá de Henares, Spain Background: Osteoarthritis (OA) is the most common joint disease and leading cause of disability. Intra-articular (IA) administration of hyaluronic acid (HA) or corticosteroids (CS) have been previously studied, though using insufficient number of patients or short follow-up periods.Objective: We evaluate HA and CS in patients with knee OA in terms of clinical efficacy over 12 months.Methods: We used a prospective, randomized study with parallel groups. Randomized patients received IA injections of HA or betamethasone (BM). The primary outcomes were improvement in pain using Visual Analog Scale and function in the Western Ontario and McMaster University Osteoarthritis Index (Likert scale). Follow-up visits were scheduled at 3 months, 6 months, 9 months, and 12 months.Results: A total of 200 patients were included. Pain was significantly reduced in both groups at the first follow-ups. At 12 months, the mean pain reduction in the HA group was 33.6% (95% CI: 31.1–36.1) compared to 8.2% (95% CI: 5.2–11.1) in BM (P<0.0001). Function improvement was higher in HA through every visit, and mean improvement at 12 months was 47.5% (95% CI: 45.6–49.3) in HA patients vs 13.2% (95% CI: 11.4–14.9) in the BM group (P<0.0001). All patients from both groups achieved the Minimal Clinically Important Improvement (MCII) for both pain and function up to 6 months. At 9 months and 12 months, the MCII figures were higher in HA group with ≥80% compared to ≤10% in BM group (P<0.0001). Adverse reactions were rare and related to the administration procedure.Conclusion: Both treatments effectively controlled OA symptoms. BM showed higher short-term effectiveness, while HA showed better long-term effectiveness, maintaining clinical efficacy in a large number of patients 1 year after administration.Keywords: viscosupplementation, corticosteroids, knee injection, joint disease